FORMATION OF COMMUNICATIVE AND SPEAKING COMPETENCE OF SOCIAL WORKERS IN THE PROCESS OF PROFESSIONAL TRAINING (World Science, 2020)
The article analyses the levels of communication skills of future social workers at the final stage of the research. It is stated that implementation of communication and speaking training is conditioned by the necessity of forming a competent specialist who has deep theoretical knowledge, communication skills necessary for establishing constructive interpersonal interaction and providing assistance to different groups of clients, and operates innovative technologies methods of assistance. It is possible to achieve a high level of professional competence during training, through a specially organized educational process aimed at the development of professional, communication and speaking skills that form the basis of future work of a social worker. The results of the study showed positive changes in the students of the experimental group, which made it possible to conclude on the efficiency of the proposed experimental method of forming the communicative and speaking competence of future social workers in the process of professional training.